Microstructural correlation of cross rolling temperature of AT55 magnesium alloy in mechanical and formability behaviour. (September 2022) - Vignesh, P.; Abraham, Amal; Kumaran, S.
Abstract: The development of magnesium alloy includes two key aspects, such as microstructure and texture, which play vital roles in mechanical and forming behaviour. In this study, cross-rolled Mg-5Al-5Sn alloy at various temperatures (350 °C, 400 °C, and 450 °C) with a 60% reduction in thickness was investigated. The effect of cross rolling temperature on the Mg-5Al-5Sn alloy microstructure, texture, tensile properties, and formability was studied. The yield strength increases from 114 MPa to 150 MPa with decreasing rolling temperature, which is attributed to grain refinement phenomena. This finding demonstrates that the AT55 Mg alloy possesses an impact on cross rolling temperature, viz. the formability increases with increases in cross rolling temperature. The alloy processed at 350 °C shows better strength and less formability than that of the alloy processed at 450 °C ( lower strength but good formability at room temperature, with an Erichsen value of 4.3 mm). Highlights: Recrystallized grain structure was founded in cross rolled Mg-5Al-5Sn alloy. The distribution of LAGB is extremely low as the cross rolling temperature increases Development of LAGBs and the realignment of dislocations are both dynamic recovery processes Twins are visible in the alloy rolled at a relatively high temperature, i.e., 450 °C